Effect of Leadership, Work Motivation, and Organizational Culture on Performance of Puskesmas Tanjung Medan Employees - Indah Sari; Junita Lubis; Fadzil Hanafi Asnora (PT Mattawang Mediatama Solution, 2022)
The type of research used in this research is descriptive quantitative. The population in the study were all employees of the Tanjung Medan Public Health Center, totaling 43 employees. The population of this study was completed by using the total sampling method. Total sampling is a test procedure in which the number of samples is equivalent to the population. The sample in this study were all employees of the Tanjung Medan Public Health Center, totaling 43 people, so the entire population was used as a sample in this study. The value of Adjusted R square obtained is 0.628, therefore the coefficient of multiple determination test is 0.628 x 100% of 62.8%. This value implies that the variables of leadership, motivation and organizational culture affect performance by 62.8% and the remaining 38.2% is influenced by other variables.